REASONING OF THE MAIN CONSTITUENTS OF ECONOMIC MECHANISM OF STIMULATION OF PRODUCTION OF ENVIRONMENTALLY FRIENDLY AGRICULTURAL PRODUCTION - Малевич, Н. Ю. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The unsystematic irrational use of land resources in the conditions of absence of clear ecological and economic reasoning of the prospects for the development of the agrarian sector leads to the loss of agricultural land fertility level and the spread of degradation processes. Therefore, there is a need to improve the economic mechanism for stimulating the production of environmentally friendly agricultural products. The ways of improvement of the economic mechanism of stimulation of production of environmentally friendly agricultural products have been proposed. Further research should be aimed at exploring the factors that will harmonize the economic and environmental interests of business entities and society as a whole, which requires the development of a system of targeted and consistent measures at the local (regional), national and national levels